Determination of shear surface of landslides using electrical resistivity tomography - DOSTÁL, Ivan; PUTIŠKA, René; KUŠNIRÁK, David (Contributions to Geophysics and Geodesy, 2014)
Geophysical methods offer a broad spectrum of information by dealing withslope deformations. The electrical resistivity tomography (ERT) method is mainly appliedfor spatial localization of the landslide body and depicting the shear zone position. Thisarticle presents the application of the ERT method for the landslide hazardous areas bymeans of numerical modelling. Four different synthetic models with very small resistivitycontrast (30 Ohm.m/50 Ohm.m), where each model represents a different type of slopedeformation, were tested by several factors affecting the final inverse model: measurementpoint density, L1 and L2 norm and L-norm roughness filter components. The higher measurementpoints density helps mainly to detect the boundaries at greater depths. Inversemodels computed using the L1 norm bring satisfactory results for compact anomalousbodies, i.e. water saturated landslide body. In the case of subtle conductive zones, i.e.shear planes, the L2 norm based inversion is recommended. For enhanced reconstructionof skewed anomalous objects, roughness filter including a diagonal component producesmore accurate inverse image. The article also demonstrates the ability of the ERT methodto detect and describe the shape of the slope deformation even by a relative subtle resistivitycontrast.